Quality of Life in Individuals with Diabetic Foot Syndrome - Navarro-Flores, Emmanuel; Cauli, Omar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background and Objective: Diabetic foot syndrome (DFS) is a common long-term complication of diabetes mellitus. DFS has recently been associated with adverse effects that could further impair the quality of life of diabetic patients, and increase the social and economic burden, morbidity, and premature mortality of the disease. The main physio-pathological basis of DFS is due to diabetesinduced neuropathy and angiopathy in the lower limbs and feet. Patients diagnosed with DFS must significantly modify their daily habits in order to cope with signs and symptoms of DFS and this can alter their quality of life. The objective of this review is to summarize the evidence regarding the economic, physical and social limitations which can affect the quality of life (QoL) in patients with DFS, the effects of ulcers and amputations on QoL outcomes. Results: Different aspects related to DFS such as physical alterations, psychological complaints and even disorders, socio-economic difficulties can affect the quality of life of these patients. However, the QoL related to low socio-economic factors gave mixed results and physical activity, education and type of footwear can influence the outcomes. There is a general gender-dependent higher prevalence of DFS in men, although it depends on the geographical area. DFS often co-occurs with other diabetes-induced complications (retinopathy, nephropathy and cardiovascular disorders) and comorbid obesity generally worsens it. Conclusion: Accessibility to health services aimed at reducing inequalities and constant health education and promotion and care regarding psychological and socio-economic issues should be continuously undertaken for individuals with DFS in order to improve their QoL.
Keywords: gender